Winter-time particulate nitrosamines and nitramines in the atmosphere at seoul, South Korea - Choi, Na Rae; Ahn, Yun Gyong; Lee, Ji Yi; Kim, Eunhye; Kim, Soontae; Park, Seung Myung; Song, In Ho; Kim, Yong Pyo (Atmospheric Environment, 2020)
Nitrosamines and nitramines are groups of chemical compounds containing nitroso (N-NO) and nitro (N-NO2) functional groups, respectively. They exert detrimental effects on our health. Simultaneous analysis of 7 nitrosamines and 3 nitramines present in atmospheric particulate matter with an aerodynamic diameter less than or equal to the nominal value of 2.5 μm (PM2.5) at Seoul in the winter of 2018 was undertaken using gas chromatography/tandem mass spectrometry (GC/MS-MS). The daily average concentrations of nitrosamines and nitramines during the sampling period were 9.75 ± 17.77 ng/m3 (0.06–54.72 ng/m3) and 0.68 ± 0.56 ng/m3 (0.08–2.40 ng/m3), respectively. The concentrations of nitramines in the atmosphere were reported in this study for the first time and could not be compared. Among the nitrosamines, nitrosodi-methylamine (NDMA) concentrations observed in this study were high and comparable to that observed at the area with emission sources (Zonguldak, Turkey) and higher than that in an urban area (North Kensington, UK). Concentrations of other nitrosamines such as nitrosodi-ethylamine (NDEA), nitrosodi-butylamine (NDBA), nitroso-piperidine (NPIP), nitroso-pyrrolidine (NPYR), and nitrosodi-propylamine (NDPA) were similar to or lower than those noted in urban areas in the previous studies. In order to determine the relative importance of primary emissions and secondary reactions, statistical analyses such as correlation and multivariance analysis were carried out. Multivariance analysis results showed that secondary reaction might affect to the formation of the nitrosamines and nitramines in the atmosphere more than the primary emission. Furthermore, the high correlations of the nitrosamines and nitramines with HONO and NO supported the possibility of the high contribution of the secondary reactions producing the nitrosamines and nitramines.
Keywords: Aerodynamic diameters; Atmospheric particulate matter; Average concentration; Gas chromatography/tandem mass spectrometries; Primary emissions; Secondary reactions; Seoul , South Korea; Simultaneous analysis; Nitramine; Nitrogeneous organic compound; Nitrosamine; PM2.5; Seoul